Association of Portal Venous System Thrombosis with Endoscopic Variceal Treatment - Risa Dewi, Risa Dewi; Khairunisa, Khairunisa (International Medical Journal Corp. Ltd, 2024)
Background: The association between portal venous system thrombosis and endoscopic variceal treatment has garnered significant attention in recent years, reflecting the complexities of managing portal hypertension and its complications. Literature Review: The literature presents a comprehensive exploration of the association between portal venous system thrombosis and endoscopic variceal treatment, emphasizing the complexities involved in managing portal hypertension and its complications. The introduction highlights the challenges faced by clinicians, especially in non-cirrhotic patients, where traditional endoscopic interventions may be inadequate. For instance, the findings from the study by (Caronna et al., 2008) indicate that endoscopic sclerotherapy fails in about 15% of non-cirrhotic cases, necessitating alternative interventions like portosystemic shunts. Conclusion: Ultimately, the literature indicates a clear need for individualized, patient-centered approaches to managing portal hypertension and its complications. The integration of various treatment modalities, including endoscopic, interventional radiology, and emerging techniques, is essential for optimizing patient care and outcomes. The collective insights from these studies reflect the evolving landscape of treatment options available for patients with portal venous system thrombosis, underscoring the necessity for continuous research and adaptation of clinical practices.